A winter's promise ebook - Dabos, Christelle (Mirror Visitor Quartet., 2023)
"A stunningly atmospheric fantasy that doubles as an exceptional character study . . . we can't wait to see where Dabos takes it next." — Entertainment Weekly ("The 10 Best YA Books of 2018") One of Publishers Weekly 's Best YA Books of the Year A National Indie Bestseller Lose yourself in the fantastic world of the arks and in the company of unforgettable characters in this French runaway hit, Christelle Dabos' The Mirror Visitor quartet. Plain-spoken, headstrong Ophelia cares little about appearances. Her ability to read the past of objects is unmatched in all of Anima and, what's more, she possesses the ability to travel through mirrors, a skill passed down to her from previous generations. Her idyllic life is disrupted, however, when she is promised in marriage to Thorn, a taciturn and influential member of a distant clan. Ophelia must leave all she knows behind and follow her fiancé to Citaceleste, the capital of a cold, icy ark known as the Pole, where danger lurks around every corner and nobody can be trusted. There, in the presence of her inscrutable future husband, Ophelia slowly realizes that she is a pawn in a political game that will have far-reaching ramifications not only for her but for her entire world. The World of the Arks Long ago, following a cataclysm called the Rupture, the world was shattered into many floating celestial islands, now known as arks. Over each, the spirit of an omnipotent and immortal ancestor abides. The inhabitants of these arks each possess a unique power. Ophelia, with her ability to read the pasts of objects, must navigate this fantastic, disjointed, perilous world using her trademark tenacity and quiet strength.